Manajemen Dinas Pemuda Dan Olahraga Provinsi Sumatera Barat Dalam Meningkatkan Prestasi Olahraga - Hamdi Fadjri; Hastria Effendi; Sonya Nelson; Liza Liza (JURNAL STAMINA, 2022)
This research was conducted to see the description of Management such as Planning, Organizing, Mobilizing and Supervising the Youth and Sports Office of West Sumatra Province in improving sports performance. So this research was carried out in order to find out the description of the Sports Management Office of Youth and Sports in improving Sports Achievement This is a descriptive qualitative research project., the exploration was done on 23 – 27 July 2021, which was carried out at the Youth and Sports Office of West Sumatra Province. This study took 4 informants. Data analysis techniques in this study are data reduction, display, drawing/verification. Data collection techniques in this study are observation, interviews and documentation. The results showed that the implementation of the POAC Management Function carried out by the Youth and Sports Office was going well, the planning was good but not all strategic plans could be carried out, the organization was run well, the movement was good but no researchers were able to get technical policies carried out in the field of sports achievements, supervision both from the employee side and with the KONI. The problems that occur are incomplete facilities and infrastructure so that they cannot accommodate the needs of athletes and coaches, the lack of cooperation from the private sector to obtain additional funds which results in the lack of athletes being able to compete in national championships, and only relying on the APBD to accommodate the needs of athletes and players